2002
DOI: 10.1177/0011392102050003008
|View full text |Cite
|
Sign up to set email alerts
|

Gender Relations and Technological Change in Asia

Abstract: Gender Relations and Technological Change in AsiaS ocial changes are just as dramatic as economic and technological transformation. Technological change can also facilitate social change, turning patriarchy into 'a contested domain, rather than a sphere of cultural reproduction, leading to fundamental redefinitions of gender relations, family and sexuality' (Castells, 2000: 2-3). In particular, advances in information technologies have the potential to change the organization of work. We will look at the effec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
26
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(30 citation statements)
references
References 9 publications
1
26
0
1
Order By: Relevance
“…Moreover, ICTs help in creating women's leadership, and participation in community and economic development (Anitha & Sundharavadivel, 2012). Most previous research, based mainly on national case studies, has indicated that ICTs increase employability and thus women's empowerment can be advanced (Arun & Arun, 2002;Hafkin & Taggart, 2001;Huyer & Carr, 2002;Islam, 2015;Kelkar & Nathan, 2002;Njelekela & Sanga, 2015;Shirazi, 2012;Suhaida et al, 2013;Umrani & Ghadially, 2003;Wamala, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, ICTs help in creating women's leadership, and participation in community and economic development (Anitha & Sundharavadivel, 2012). Most previous research, based mainly on national case studies, has indicated that ICTs increase employability and thus women's empowerment can be advanced (Arun & Arun, 2002;Hafkin & Taggart, 2001;Huyer & Carr, 2002;Islam, 2015;Kelkar & Nathan, 2002;Njelekela & Sanga, 2015;Shirazi, 2012;Suhaida et al, 2013;Umrani & Ghadially, 2003;Wamala, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In line with the proven role of digital networks in feminist movements, technology enables women to participate meaningfully for their voice to be heard (Harcourt, 1999). Some researchers have contended that internet has the potential to entirely redefine the traditional gender roles, especially for those women who have limited skills or those who lack the resources to get proper higher education (Kelkar & Nathan, 2002).…”
Section: Cyberfeminismmentioning
confidence: 99%
“…they take decisions of their own and within limited terms. Kelkar and Nathan (2002) observe that the effects of women"s entry into the IT Sector have augmented their household income enlarging their bargaining power within the households. Besides, larger quantum of work participation rate among the women furthers their social mobility.…”
Section: Opportunities Provided For Women By Itmentioning
confidence: 99%
“…As a result, an ongoing struggle brews in on them to challenge the embedded patriarchal relations and existing structural inequalities. Yet, women do not hesitate to seek constantly to balance work and domestic responsibilities with little help from their men (Kelkar and Nathan 2002;Shanker 2008).…”
Section: Opportunities Provided For Women By Itmentioning
confidence: 99%
See 1 more Smart Citation